LITERATUR REVIEW MANFAAT DARI ENTERPRISE RISK MANAGEMENT DI INDONESIA - Josin Sitinjak; Nibras Anny Khabibah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
To overcome the intricacies involved in risk management procedures, organizations adopt a risk management framework that is more effective, open, and risk-focused. One such framework that can be applied to this issue is enterprise risk management (ERM). To explore this topic, a review of pertinent literature was conducted to examine risk management, ERM, and the advantages of implementing ERM. Based on the literature review, it was revealed that the deployment of ERM can mitigate unexpected risks and enhance the organization's perceived value among stakeholders.